Can board climate-responsible orientation improve corporate carbon performance? The moderating role of board carbon awareness and firm reputation - Xia, Mengyao; Cai, Helen Huifen; Yuan, Qiong (Frontiers in Environmental Science, 2022)
Overwhelming evidence from prior research suggests the functions of the board of directors have a vital influence on carbon performance. However, very little is known about the moderating effect of board functions. This study attempts to fill this gap by developing and empirically testing a conceptual model that highlights the role of board carbon awareness and firm reputation in the relationship between board climate-responsible orientation (BCO) and carbon performance. Using a fixed effect model to analyze data from 665 US listed firms covering a period of 2010–2019, we find that BCO and carbon performance show a U-shaped non-linear relationship. Increased experience of BCO improves corporate carbon performance. The results also provide evidence of the moderating effect of carbon awareness and firm reputation on the relationship between BCO and carbon performance. Carbon awareness reduces symbolic emission reduction actions in carbon management, while, firm reputation will cause symbolic emission reduction actions. Besides, splitting the sample according to firm size and carbon dependency shows BCO has a better effect on the carbon performance of small or medium-sized and high carbon-dependency firms. The findings have important implications for managers to use firm governance mechanisms to improve carbon performance.